'That's how it works here': The place of religion in publicly managed second‐level schools in Ireland. (19th October 2018) - McCormack, O.; O'Flaherty, J.; O'Reilly, B.; Liston, J.
Abstract : This article problematises the place of religion within publicly managed Education and Training Board (ETB) schools in the Republic of Ireland. The study draws on interview data from 43 school personnel across 18 ETB second‐level schools, as well as eight interviews with ETB Education/Chief Executive Officers. Having established the legal and historical contexts, the place of religion is explored from the perspective of school life and prescribed curriculum. Across the 18 schools, the prescribed curriculum for Religious Education did not take the form of 'faith formation'. Rather, focus was placed on exploring all world religions. However, this compares with the role of religion within the life of the school; 14 of the 18 participating schools had religious dimensions as part of school life. Half of these schools ( n  = 7) were Designated Community Colleges, while the remainder were Non‐Designated ( n  = 7). The religious dimension was always Catholic in nature. Bar a few exceptions, the role of religion within the life of the school remained largely unquestioned by school personnel. The article explores the findings in light of the legislative and historical contexts.